Why Children Are Not Always Epistemically Vigilant: Cognitive Limits and Social Considerations. (12th July 2016) - Jaswal, Vikram K.; Kondrad, Robyn L.
Abstract: Young children are thought to be motivated to avoid individuals who have been wrong in the past so as to minimize the risk of being misinformed. Yet they sometimes act on testimony from formerly inaccurate informants. Most explanations for this behavior have focused on limits in children's ability to process inaccurate testimony, such as difficulty inhibiting the normally appropriate bias to believe what people say. In this article, we argue that children may also use information from formerly inaccurate informants because doing so allows them to achieve other, nonepistemic goals. Testimony not only offers children a way to learn about the world, but it also offers them a way to pursue social goals that may be separate from learning.